Boosting Recombinant Inclusion Body Production—From Classical Fed-Batch Approach to Continuous Cultivation - Kopp, Julian; Kolkmann, Anna-Maria; Veleenturf, Patrick Gwen; Spadiut, Oliver; Herwig, Christoph; Slouka, Christoph (Frontiers in Bioengineering and Biotechnology, 2019)
State of the art microbial recombinant protein production is regularly performed in fed-batch based cultivations. However, these cultivations suffer from highly time-dependent changes in productivity and product quality, leading to high variations in the downstream process. Continuous biomanufacturing offers the possibility of a time independent process, boosting the time-space-yield of the recombinantly produced protein and further reducing costs for production, also as downstream gets more predictive. In the current work, the continuous production of a pharmaceutically relevant protein in form of an inclusion body in E. coli BL21(DE3) was investigated in single vessel cultivations by varying dilution rates using glycerol as carbon source, inducer (lactose or IPTG) and respective inducer concentrations. Attempts to increase low specific productivities observed in single vessel continuous cultivations, led to the establishment of a continuously operated cascade of two stirred tank reactors to spatially separate biomass formation from recombinant protein production. Process performance was substantially improved compared to a single vessel chemostat culture, as specific productivity and space-time yield were boosted using an optimized cascaded process by about a factor of 100. This study shows the potential of a two-stage continuous process as promising alternative to benchmark fed-batch processes achieving constant inclusion body production at a time-independent level.